2015
DOI: 10.1111/cei.12628
|View full text |Cite
|
Sign up to set email alerts
|

Circulating mitochondrial DNA in serum of patients with granulomatosis with polyangiitis

Abstract: Neutrophil is a key cell in pathophysiology of granulomatosis with polyangiitis. Recently, neutrophil extracellular traps were described in this disease. Mitochondrial DNA is also released during traps formation. We measured circulating cell-free mitochondrial and genomic DNA in serum of patients with granulomatosis with polyangiitis. Subjects with the disease (14 active and 11 in remission stage) and 10 healthy controls were enrolled. Quantitative real-time polymerase chain reaction (PCR) was used to measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…The ability of mtDNA to activate proinflammatory signaling cascades links it to chronic inflammatory diseases, such as rheumatoid arthritis, systemic lupus erythematosus, and granulomatosis with polyangiitis, and atherosclerosis . For a recent review on mtDNA‐specific activation pathways see Boyapati et al., 2017 …”
Section: Np Exposure Leads To Release Of Endogenous Danger Signalsmentioning
confidence: 99%
“…The ability of mtDNA to activate proinflammatory signaling cascades links it to chronic inflammatory diseases, such as rheumatoid arthritis, systemic lupus erythematosus, and granulomatosis with polyangiitis, and atherosclerosis . For a recent review on mtDNA‐specific activation pathways see Boyapati et al., 2017 …”
Section: Np Exposure Leads To Release Of Endogenous Danger Signalsmentioning
confidence: 99%
“…The presence of NETs in glomeruli in AAV have then been confirmed by others (Yoshida et al 2013, O'Sullivan et al 2015, Tang et al 2015, and NETs have also been shown to be present in skin lesions (Abreu-Velez et al 2009, Sangaletti et al 2012) and thrombi , Imamoto et al 2014) from patients. In addition to the histological findings of NETs in biopsies, elevated levels of NETs in the circulations have also been identified in patients (Table I) (Kessenbrock et al 2009, Surmiak et al 2015, Surmiak et al 2016). Similar results as for NETs have been obtained for NET-associated components such as HMGB1, calprotectin, PR3, MPO, and NE as well as mtDNA when measured separately in the circulation (Table 1) (Henshaw et al 1994, Haubitz et al 1997, Ohlsson et al 2003, Wibisono et al 2010, Bruchfeld et al 2011, Pepper et al 2013, Surmiak et al 2016).…”
Section: Presence In Biopsies and Plasma/serummentioning
confidence: 98%
“…In addition to their role as antimicrobial agents, NETs of both nuclear and mitochondrial origin have been connected to autoinflammatory or autoimmune diseases (Gupta et al 2005, Kessenbrock et al 2009, Dwivedi et al 2012, Khandpur et al 2013, Leffler et al 2013, Sur Chowdhury et al 2014, Surmiak et al 2015, Lood et al 2016, and have therefore been referred to as a double edged sword of innate immunity (Kaplan and Radic 2012).…”
Section: Extracellular Trapsmentioning
confidence: 99%
See 2 more Smart Citations